An operational semantics for a fragment of PRS - de Silva, Lavindra; Meneguzzi, Felipe; Logan, Brian (2018)
The Procedural Reasoning System (PRS) is arguably the ﬁrst implementation of the Belief–Desire–Intention (BDI) approach to agent programming. PRS remains extremely inﬂuential, directly or indirectly inspiring the development of subsequent BDI agent programming languages. However, perhaps surprisingly given its centrality in the BDI paradigm, PRS lacks a formal operational semantics, making it difﬁcult to determine its expressive power relative to other agent programming languages. This paper takes a ﬁrst step towards closing this gap, by giving a formal semantics for a signiﬁcant fragment of PRS. We prove key properties of the semantics relating to PRS-speciﬁc programming constructs, and show that even the fragment of PRS we consider is strictly more expressive than the plan constructs found in typical BDI languages.